If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x + -1(3x + 5) = 0 Reorder the terms: 6x + -1(5 + 3x) = 0 6x + (5 * -1 + 3x * -1) = 0 6x + (-5 + -3x) = 0 Reorder the terms: -5 + 6x + -3x = 0 Combine like terms: 6x + -3x = 3x -5 + 3x = 0 Solving -5 + 3x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '5' to each side of the equation. -5 + 5 + 3x = 0 + 5 Combine like terms: -5 + 5 = 0 0 + 3x = 0 + 5 3x = 0 + 5 Combine like terms: 0 + 5 = 5 3x = 5 Divide each side by '3'. x = 1.666666667 Simplifying x = 1.666666667
| 8x^2+9x+3=0 | | y=8x^2+26x | | 9n-29=43 | | 5n+6p+7n+p= | | (n+3)*9=45 | | (n-8)*6=30 | | x^2+12x-25=0 | | -2+-2=-2(x-5)-6 | | 77-3x=24x+14 | | 5x+35=14x-36 | | 1+2[3(x-1)-5(2x-3)]=2x-7 | | 4x+5-10x=8+3x+12 | | 5x+31=tx+11 | | 4x^2+7x-8=0 | | 8b-4(b-2)=42 | | -6-20=-2n | | 2x+10=110-10x | | 8x+9=2x-13 | | 4x=8x+6 | | x+4+5+2=3+2+2x | | 2*(x+3)-3(x+1)=x-13 | | b(b+2)+4b^2=5b^2+9b+8 | | 10x-13=3x-7 | | y=2x^3-7x^2-15x | | x+11=8+x | | x+11=8+c | | n-9=7 | | n+27=44 | | a-4=3a-6 | | 5y-10=2y-3x+11 | | (11x)=(5x+30) | | 2x+8=8x-1 |